Quality of life of patients with congenital heart diseases - Silva, Ana (2011)
Objectives: To assess the perception of the quality of life of adolescents and young adults with congenital heart disease and to examine the variables that have a negative impact on it and that add a resilience effect. Methods: A total of 22 male and 18 female patients, aged 12-26 years, of whom 27 were admitted to surgery and 13 were not, participated in this study. All patients had complete medical records and were interviewed once; demographic and clinical data were collected, and patients filled a questionnaire on quality of life, the WHOQOL-BREF, and underwent an interview on social support, educational style, self-image, functional limitations, and emotional adjustment. Results/Conclusions: Our patients showed a better perception of quality of life than did the general population, on the basis of psychological, social relationship and environment scales. Older patients hold a better perception of quality of life on the psychological scale. Cyanosis did not show any significant impact over perception of quality of life decay; however, the number of surgical procedures and the persistence of moderate-to-severe residual injuries had considerable detrimental effect. Social support had an impact on increasing resilience, promoting adjustment to illness. Several factors may play a role in adjustment to congenital heart disease, either improving the perception of quality of life or worsening it. We may conclude that some buffer variables on congenital heart disease may play roles in increasing the perception of quality of life of patients during their lifetime, social support probably explaining why the perception of quality of life is better than in the normal population. The number of surgeries and the moderate-to-severe residual injuries, however, reverted that effect.